Boundary layer flow of a non-Newtonian fluid over an exponentially stretching sheet with the presence of a heat source/sink - Vinod Y．; K.R. Raghunatha; Suma Nagendrappa Nagappanavar; Nodira Nazarova; Manish Gupta; Sangamesh (Partial Differential Equations in Applied Mathematics)
This study examines the magnetohydrodynamic (MHD) boundary layer flow and heat transfer of a Casson fluid, a non-Newtonian fluid, over an exponentially stretching sheet, incorporating the effects of a heat source or sink and thermal radiation. The governing equations, formulated as nonlinear partial differential equations, capture the Casson fluid's properties, magnetic field effects, and radiative heat transfer. These equations are transformed into a system of nonlinear ordinary differential equations using similarity transformations, reducing the problem to a finite domain. This finite domain is effectively solved using the Taylor wavelet method, ensuring high accuracy. Key parameters, including the magnetic field, Casson fluid, radiation, heat source/sink, and Prandtl number, are analyzed to assess their impact on velocity, temperature profiles, surface skin friction, and heat transfer rates. The results show that increasing the magnetic field reduces velocity due to Lorentz forces and raises skin friction. Higher Casson fluid parameters lower the velocity gradient at the surface, reducing skin friction. Thermal radiation enhances temperature distribution, while a heat source increases thermal boundary layer thickness and temperature. Conversely, a heat sink reduces both, improving heat transfer efficiency. The Nusselt number increases with higher Prandtl numbers and heat sink parameters, indicating enhanced heat transfer. The results align with previously published findings, validating the model. This research is significant for MHD flows of non-Newtonian fluids, with applications in polymer extrusion, metal casting, and cooling technologies. The inclusion of thermal radiation and heat source/sink effects broadens its relevance to energy-intensive systems such as nuclear reactors and thermal insulation. The study underscores the effectiveness of the Taylor wavelet method for solving complex boundary layer problems, offering a valuable framework for future research. It bridges the gap between theoretical fluid dynamics and practical heat transfer applications, providing insights for optimizing systems involving Casson fluids under thermal effects.